2021
DOI: 10.3390/antibiotics10101213
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Effect of an Oxytetracycline Treatment on the Gut Microbiome and Antimicrobial Resistance Gene Dynamics in Nile Tilapia (Oreochromis niloticus)

Abstract: Antibiotics play a vital role in aquaculture where they are commonly used to treat bacterial diseases. However, the impact of antibiotic treatment on the gut microbiome and the development of antimicrobial resistance in Nile tilapia (Oreochromis niloticus) over time remains to be fully understood. In this study, fish were fed a single treatment of oxytetracycline (100 mg/kg/day) for eight days, followed by a 14-day withdrawal period. Changes in the distal gut microbiome were measured using 16S rRNA sequencing.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 81 publications
(97 reference statements)
4
15
0
Order By: Relevance
“…In short, the results showed that FFC treatment caused a reduction in all the gut microbial counts but there was a clear shift in the gut microbiome toward well-known putative pathogens. In support of our findings, the shifts in the gut microbiome toward well-known putative pathogens following different antibiotic treatments were reported in the earlier studies on freshwater fish ( Zhou et al, 2018 ; Sáenz et al, 2019 ; Payne et al, 2021 ). Simultaneously, the observed reduction in the bacterial count on TCBS agar showed that FFC has good antagonistic activity against the major marine fish pathogens (belonging to Vibrionacetheae family).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In short, the results showed that FFC treatment caused a reduction in all the gut microbial counts but there was a clear shift in the gut microbiome toward well-known putative pathogens. In support of our findings, the shifts in the gut microbiome toward well-known putative pathogens following different antibiotic treatments were reported in the earlier studies on freshwater fish ( Zhou et al, 2018 ; Sáenz et al, 2019 ; Payne et al, 2021 ). Simultaneously, the observed reduction in the bacterial count on TCBS agar showed that FFC has good antagonistic activity against the major marine fish pathogens (belonging to Vibrionacetheae family).…”
Section: Discussionsupporting
confidence: 92%
“…Contrariwise, cutting-edge research in terrestrial animals has amply demonstrated the adverse effect of antibiotic treatment in disrupting the healthy gut microbiome of the host ( Holman et al, 2019 ). As the gut microbiome serves several vital biological and physiological functions for the host, understanding the intended and unintended consequences of antibiotic treatment on the gut microbiome is vital to support the overall health and welfare of the farmed animals ( Payne et al, 2021 ). The antibiotic treatment can also cause the emergence of antimicrobial resistance (AMR) in gut microbes, raising additional concerns about consumer and environmental safety ( Cabello et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…The decrease in Proteobacteria can be attributed to the abundance of fish pathogens that belong to the particular phylum [ 22 , 23 , 24 ]. Additionally, the decrease in the abundance of Fusobacteria can demonstrate the unregulated effect of OTC in targeting other bacterial groups [ 25 ]. However, the abundance of Tenericutes and Firmicutes was higher in OTC-treated fish.…”
Section: Discussionmentioning
confidence: 99%
“…In fish, antibiotic exposure has also been experimentally shown to exert selective pressures on skin, gill, and gut microbiomes. Dietary doses of oxytetracycline (100 mg/kg) (Payne et al 2021) and sulfamonomethoxine (200 and 300 mg/kg) (Ming et al 2020) given to Nile tilapia were found to cause minimal changes to alpha and beta diversity metrics of gut microbial communities; however, these exposures were not found to cause altered abundance in taxa for genera containing reputed pathogens. Further experimental evidence, however, has shown perturbation of skin and gut microbiomes, with enrichment of potentially opportunistic pathogens, following oral exposure of yellowtail kingfish Seriola lalandi to an antibiotic cocktail of oxytetracycline (200 mg/kg), erythromycin (50 mg/kg), and metronidazole (50 mg/kg).…”
Section: Effects Of Antibiotics On Fish Microbiomesmentioning
confidence: 94%